THE ROLE OF ORGANIZATIONAL FLEXIBILITY IN ORGANIZATIONAL SUCCESS WITHIN THE FRAMEWORK OF THE SUSTAINABLE DEVELOPMENT MODEL: DESCRIPTIVE AND ANALYTICAL RESEARCH IN THE MINISTRY OF INDUSTRY AND MINERALS (World Economics and Finance Bulletin, 2023)
The research aims to test the relationship and impact of organizational flexibility as an independent variable on organizational success as a responsive variable and the presence of sustainable development as a mediating variable in the Ministry of Industry and Minerals, and then try to come up with a set of recommendations that contribute to the relationship. This research was applied to a group of members of the councils of the Ministry of Industry and Minerals, who numbered (125) individuals and the researcher used the questionnaire as a main tool for collecting information and measuring the level of the research variables and the relationships of correlation and influence between them. In order to process the data and information, the statistical analysis program (SPSS) was used to reach the results through a group of statistical methods. The research reached several results, which were: The most important of which is the high level of research variables (organizational flexibility, sustainable development, organizational success) in the Ministry of Industry and Minerals, in addition to verifying the existence of highly significant correlations and influence between the research variables and their sub-dimensions, and arriving at a set of recommendations that support this relationship and in a way that enhances the Ministry’s practices. Industry and minerals in achieving regulatory success within the framework of sustainable development